Investigating STEM Career Content in Indonesian Science Junior High School Textbooks - Riski Amalia; Remanda Arya Wisutama; Nurul Fitriyah Sulaeman; Riskan Qadar (Jurnal Pendidikan Fisika, 2023)
This study aims to analyze the STEM career content in science junior high school textbooks commonly used for the seventh grade students in Indonesian schools. This research was qualitative descriptive research with content analysis. The analysis was carried out on five books that are widely used in the school. Reports and activities were analyzed using content analysis through an assessment rubric based on Social Cognitive Career Theory (SCCT) which are awareness, relevance, engagement and self-efficacy. The analysis showed that the STEM career content in science junior high school textbooks were still lacking. The books were not sufficient in presenting content about careers in the STEM field. These results indicated that none of the five textbooks had fulfilled the four aspects of STEM career. The aspect most commonly found in the textbooks was self-efficacy, and the most observed STEM career content was found in the earliest chapter, which is Nature of Science. These findings highlight the importance of career oriented in science lesson that illustrated in the textbook to enhance students’ perception and enthusiasm in pursuing STEM career in the future.